Promoter methylation of serotonin transporter gene is associated with obesity measures: a monozygotic twin study - Zhao, J (Nature Publishing Group, 2013)
OBJECTIVE: Epigenetic mechanisms are increasingly being recognized as an important factor for obesity. The serotonin transporter gene (SLC6A4) has a critical role in regulating food intake, body weight and energy balance. This study examines the potential association between SLC6A4 promoter methylation and obesity measures in a monozygotic (MZ) twin sample. METHODS: We studied 84 MZ twin pairs drawn from the Vietnam Era Twin Registry. Obesity measures include body mass index (BMI), body weight, waist circumference (WC) and waist-hip ratio (WHR). The SLC6A4 promoter methylation profile in peripheral blood leukocytes was quantified by bisulfite pyrosequencing. The association between methylation variation and obesity parameters was examined by mixed-model regression and matched pair analysis, adjusting for age, smoking, alcohol consumption, physical activity and total daily energy intake. Multiple testing was controlled using the adjusted false discovery rate (q-value). RESULTS: Mean methylation level was positively correlated with BMI (r=0.29; P=0.0002), body weight (r=0.31; P<0.0001) and WC (r=0.20; P=0.009), but not WHR. Intra-pair differences in mean methylation were significantly correlated with intra-pair differences in BMI, body weight and WC, but not WHR. On average, a 1% increase in mean methylation was associated with 0.33 kg m(−2) increase in BMI (95% CI: 0.02–0.65; P=0.03), 1.16 kg increase in body weight (95% CI, 0.16–2.16; P=0.02) and 0.78 cm increase in WC (95% CI, 0.05–1.50; P=0.03) after controlling for potential confounders. CONCLUSIONS: SLC6A4 promoter hypermethylation is significantly associated with an increased prevalence of obesity within a MZ twin study.